2020
DOI: 10.1007/s11274-020-02911-5
|View full text |Cite
|
Sign up to set email alerts
|

Yeast biofilm in food realms: occurrence and control

Abstract: In natural environments, microorganisms form microbial aggregates called biofilms able to adhere to a multitude of different surfaces. Yeasts make no exception to this rule, being able to form biofilms in a plethora of environmental niches. In food realms, yeast biofilms may cause major problems due to their alterative activities. In addition, yeast biofilms are tenacious structures difficult to eradicate or treat with the current arsenal of antifungal agents. Thus, much effort is being made to develop novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 101 publications
0
30
0
1
Order By: Relevance
“…As various yeast species with spoilage potential can form biofilms (e.g., [ 69 , 70 ]), we tested the isolates assigned to these species and representatives of the other species for biofilm formation by culturing them in liquid media without agitation. All K. fluxuum , P. membranifaciens , R. mucilaginosa and Metschnikowia isolates, but none of the isolates of the other species, formed pellicles (films) on the surface of the medium at both glucose concentrations (2 and 50%) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As various yeast species with spoilage potential can form biofilms (e.g., [ 69 , 70 ]), we tested the isolates assigned to these species and representatives of the other species for biofilm formation by culturing them in liquid media without agitation. All K. fluxuum , P. membranifaciens , R. mucilaginosa and Metschnikowia isolates, but none of the isolates of the other species, formed pellicles (films) on the surface of the medium at both glucose concentrations (2 and 50%) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Within the layer, the cells of these less osmotolerant species can propagate and form biofilms. Many yeast species can form biofilms by aggregating their cells and/or producing pseudohyphae [ 70 ]. We found that the K. fluxuum and P. membranifaciens biofilms consisted of adhered cells, and the Metschnikowia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Among Pichia isolates, a strain of P. membranifaciens was also found. It can spoil wine and other fermented foods with the production of biofilm on the surface of wines and undesirable volatile compounds such as volatiles phenols [ 29 , 37 ]. It has also been previously studied for biofilm formation on stainless steel in filler implants in breweries [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides carotenoids production and biocontrol activities, also phenotypes not previously evaluated on red yeast are indeed essential for the identification of the most suitable biotechnological process for their exploitation. As recently reviewed by [40], yeast biofilm formation in food and food processing plants could be considered as a positive or negative phenotype. Here, the high biofilm forming ability coupled with the high carotenoid content of the strains in cluster 5 suggests their possible utilization for the continuous production of carotenoids in bioreactors where yeast cells are immobilized on inert surfaces [61].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of yeast to form biofilm on biotic and abiotic surfaces is a phenotypic character with both negative and positive implications. It is undesired within the clinical realm [35][36][37] but also in food processing and drinking water distribution systems [38][39][40]. In contrast, biofilm formation is required in some food processes including the maturation of cheeses and sausages [41][42][43] and the biological aging of wine [44].…”
Section: Biofilm Forming Abilitymentioning
confidence: 99%